2023
DOI: 10.3390/jof9121142
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis and Bacillus amyloliquefaciens Mix Suppresses Rhizoctonia Disease and Improves Rhizosphere Microbiome, Growth and Yield of Potato (Solanum tuberosum L.)

Vladislava S. Maslennikova,
Vera P. Tsvetkova,
Evgenia V. Shelikhova
et al.

Abstract: Black scurf and stem canker caused by Rhizoctonia solani is a significant disease problem of potatoes. Currently, chemical methods are the primary means of controlling this pathogen. This study sought to explore an alternative approach by harnessing the biocontrol potential of a bacterial mix of Bacillus subtilis and Bacillus amyloliquefaciens against black scurf, and to determine their effect on rhizosphere microorganisms of soil microbiota. This study showed that these bacteria demonstrate antagonistic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Similarly, Wang et al (2023) reported that B. velezensis B19 was highly antagonistic to Panax notoginseng (Sanqi) root rot. Maslennikova et al (2023) found that a mix of B. subtilis and B. amyloliquefaciens suppressed R. solani, and improved the physiology of potato plants. El Hadrami et al (2010) and Liu et al (2016) showed that chitosan played a major role in enhancing plant resistance to diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Wang et al (2023) reported that B. velezensis B19 was highly antagonistic to Panax notoginseng (Sanqi) root rot. Maslennikova et al (2023) found that a mix of B. subtilis and B. amyloliquefaciens suppressed R. solani, and improved the physiology of potato plants. El Hadrami et al (2010) and Liu et al (2016) showed that chitosan played a major role in enhancing plant resistance to diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Choosing the best microbial strain is critical, as it has direct impact on colonization density and effectiveness. Bacillus, a heterotrophic saprophyte, is common in soil and aquatic habitats, particularly in soils, where it exists as latent spores at temperatures near 0°C, allowing these bacteria to resist adverse environmental conditions (Maslennikova et al, 2023). Bacillus velezensis, particularly strains GB03, QST 713, FZB42, and D747, has commercial potential for disease biocontrol and host plant growth promotion (Vallejo, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary research found that Bacillus velezensis LJ02 reduces the occurrence of powdery mildew [12]. Bacillus mixed or compound with other biocontrol bacteria has a better disease control effect than a single strain [40]. The combined application of microbial agents with different mechanisms of action, different growth conditions and different ecological adaptability has stronger defense, coordination inhibition, and improve the disease prevention and stability [41].…”
Section: Discussionmentioning
confidence: 99%